2011
DOI: 10.4103/0972-2327.85873
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the stigma of epilepsy

Abstract: Stigma and resultant psychosocial issues are major hurdles that people with epilepsy confront in their daily life. People with epilepsy, particularly women, living in economically weak countries are often ill equipped to handle the stigma that they experience at multiple levels. This paper offers a systematic review of the research on stigma from sociology and social psychology and details how stigma linked to epilepsy or similar conditions can result in stereotyping, prejudice and discrimination. We also brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 37 publications
2
41
0
1
Order By: Relevance
“…Social stigma and discrimination of PWE occur in both developed and developing countries [5,6]. In many countries, this disorder is still shrouded in secrecy and patients prefer not to reveal or discuss their condition [7]. In Malaysia, a survey to assess public awareness and knowledge reported that even though there was a high awareness of the condition, many of the 839 respondents had negative attitudes and poor knowledge on epilepsy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Social stigma and discrimination of PWE occur in both developed and developing countries [5,6]. In many countries, this disorder is still shrouded in secrecy and patients prefer not to reveal or discuss their condition [7]. In Malaysia, a survey to assess public awareness and knowledge reported that even though there was a high awareness of the condition, many of the 839 respondents had negative attitudes and poor knowledge on epilepsy [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Some, though not all, people with epilepsy feel stigmatised by their condition. 12 The relationship between the severity of epilepsy and its impact on QOL is complex and may be determined by a number of different factors. 13 QOL in patients with epilepsy is a function of an interaction of factors which include clinical variables (e.g.…”
mentioning
confidence: 99%
“…Yet they encounter individuals who hold firm beliefs of supernatural associations with epileptics. As future health care providers, they should be trained appropriately to deal with situations which might put the patients' psychological conditions at stake due to social burden [1]. Hence, prompt steps to spread awareness among the population include the proper attitude and understanding of medical professionals towards epileptic patients as well as counseling of common man so as to improve their approach towards epileptics because eradicating ignorant beliefs and practices is essential to improving the quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the commonest neurological disorders with marked sociocultural stigma [1]. It is a neurodegenerative disease manifesting as seizures that lack any toxic grounds.…”
Section: Introductionmentioning
confidence: 99%